An Integrated Principal Leadership Model for Building a Character-Based School Climate in Elementary Schools - Anto Akbar; Bunyamin Maftuh; Warlim Warlim; Tedi Supriyadi; Saepul Anwar (PT. Pusmedia Group Indonesia, 2026)
The success of character development among elementary school students is greatly influenced by the creation of a supportive school environment and effective principal leadership. This study aims to describe and analyze the principal’s leadership model in fostering a character-based school climate in elementary schools. The research was conducted from February to May 2026 using a qualitative approach and case study method at SDN 201 Sukaluyu, Bandung. The research participants consisted of one principal, five teachers, two parents, and one school committee member selected through purposive sampling. Data were collected through semi-structured interviews, observations, and document analysis, then analyzed using the Miles, Huberman, and Saldaña interactive model, which includes data condensation, data presentation, and the drawing and verification of conclusions. The credibility of the findings was strengthened through source triangulation and methodological triangulation. The research results indicate that the principal’s leadership plays a strategic role in fostering a character-based school climate through six mutually integrated components: a character vision grounded in discipline and independence; the principal’s exemplary leadership; an integrated character education program; collaboration among the school, parents, and the school committee; continuous monitoring; and the establishment of a school climate characterized by religiosity, discipline, independence, environmental care, and collaboration. Character education is implemented through various integrated programs, including religious activities, the Adiwiyata Program, the Environment-Based School Program, literacy activities, the Pancasila Student Profile Strengthening Project (P5), and the Pancawaluya Task Force. This study produced a model of school principal leadership that integrates a character-based vision, exemplary leadership, character-based programs, school-community collaboration, and continuous monitoring in building a character-based school climate. The findings of this study contribute to the development of research on educational leadership and character education and provide practical implications for elementary schools in strengthening student character development through a sustainable school climate.